PENINGKATAN KEMAMPUAN MEMAHAMI ALUR CERPEN MELALUI TEKNIK PENYUSUNAN KEMBALI VISUALISASI ALUR PADA SISWA SEMESTER I UNIVERSITAS ASAHAN - Heni Subagiharti (Jurnal Akrab Juara, 2019)
This study aims to describe the increase in the ability of Asahan University Semester I students in understanding the short story flow after participating in learning that is designed with the technique of rearranging flow visualization in learning after participating in learning with the technique of rearranging flow visualization. Through this research, students are expected to be able to understand the storyline well. In this classroom action research, students are said to be successful in learning if they have reached the classical learning completeness value of 75. The subject of this study is the Asahan University Semester I student. The research design used was the design of Class Action Research conducted in two cycles. Research data collection uses test techniques. The results of this study are that there is an increase in students' ability to understand the short story flow in students of Asahan University Semester I starting from cycle I and cycle II. Student grades increased from 77.72 to 84.39. This means an increase of 06.67%. The test results understand the short story flow of cycle I with an average value reaching 77.72 included in the sufficient category because it is in the range of 61-75. The test results understand the short story flow in cycle II obtained an average value of 84.39. Based on these data it can be seen that the average value is included in the good category which is in the range between 76-90. The achievement of the score means that it has fulfilled and even exceeded the set target and an increase.